Automated surgical skill assessment in endoscopic pituitary surgery using real‐time instrument tracking on a high‐fidelity bench‐top phantom - Adrito Das; Bilal Sidiqi; Laurent Mennillo; Zhehua Mao; Mikael Brudfors; Miguel Xochicale; Danyal Z. Khan; Nicola Newall; John G. Hanrahan; Matthew J. Clarkson; Danail Stoyanov; Hani J. Marcus; et al. (Healthcare Technology Letters)
Abstract Improved surgical skill is generally associated with improved patient outcomes, although assessment is subjective, labour intensive, and requires domain‐specific expertise. Automated data‐driven metrics can alleviate these difficulties, as demonstrated by existing machine learning instrument tracking models. However, these models are tested on limited datasets of laparoscopic surgery, with a focus on isolated tasks and robotic surgery. Here, a new public dataset is introduced: the nasal phase of simulated endoscopic pituitary surgery. Simulated surgery allows for a realistic yet repeatable environment, meaning the insights gained from automated assessment can be used by novice surgeons to hone their skills on the simulator before moving to real surgery. Pituitary Real‐time INstrument Tracking Network (PRINTNet) has been created as a baseline model for this automated assessment. Consisting of DeepLabV3 for classification and segmentation, StrongSORT for tracking, and the NVIDIA Holoscan for real‐time performance, PRINTNet achieved 71.9% multiple object tracking precision running at 22 frames per second. Using this tracking output, a multilayer perceptron achieved 87% accuracy in predicting surgical skill level (novice or expert), with the ‘ratio of total procedure time to instrument visible time’ correlated with higher surgical skill. The new publicly available dataset can be found at https://doi.org/10.5522/04/26511049.